THE INFLUENCE OF MARKET RATIO ON CUMULATIVE ABNORMAL RETURNS IN COMPANIES LISTED ON THE JAKARTA ISLAMIC INDEX (JII) - Mutiah, Miftahul; Andi Ayu Frihatni; Purnamasari, Rini (Islamic Financial And Accounting Review, 2024)
This research was conducted to test whether there is an influence of earnings per share and price earnings ratio on the Cumulative Abnormal Return of 14 companies listed on the Jakarta Islamic index during 2020-2022. This research uses field research, this research uses quantitative research methods. The approach used in this research is an associative approach which aims to determine the relationship between two or more variables. With data collection techniques in the form of documentation using primary data sourced from secondary data, and processing using E-Eviws 12 (X64). There is a statistical analysis technique with 14 companies selected using the purposive sampling method registered in the Jakarta Islamic Index during 2020-2022. The research results obtained show 1) Earning Per Share has no positive influence and is not significant on Cumulative Abnormal Return. This is proven by the t-test carried out, where a value of 0.9314 > 0.05 was obtained, so it can be concluded that H1 is rejected. 2) Price Earning Ratio has no positive influence and is not significant on the Cumulative Abnormal Return value. This is proven by the t-test carried out, where a value of 0.9287 > 0.05 was obtained, so it can be concluded that H2 is rejected. 3) Simultaneously Earning Per Share and Price Earning Ratio do not have a positive and insignificant influence on Cumulative Abnormal Return which has been proven from the F-Test results where a value of 0.986304 > 0.05 is obtained, so it can be concluded that H4 is rejected.